2017
DOI: 10.18632/oncotarget.20247
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of Rnd3 in neural stem cells promotes proliferation via upregulation of Notch signaling

Abstract: Rnd3, a Rho GTPase, is involved in the inhibition of actin cytoskeleton dynamics through the Rho kinase-dependent signaling pathway. We previously demonstrated that mice with genetic deletion of Rnd3 developed a markedly larger brain compared with wild-type mice. Here, we demonstrate that Rnd3 knockout mice developed an enlarged subventricular zone, and we identify a novel role for Rnd3 as an inhibitor of Notch signaling in neural stem cells. Rnd3 deficiency, both in vivo and in vitro, resulted in increased le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The cell growth-inhibiting effect of RND3 overexpression has been demonstrated in esophageal squamous cell carcinoma cells, 23 while RND3 knockdown was found to enhance cell proliferation in glioblastoma cells and neural stem cells. 24,25 We therefore investigated whether miR-182-5p and miR-96-5p would inuence HCC cell growth in vitro by targeting RND3. Our cell viability and proliferation assay results both suggested that RND3 OE or TC-S 7001 treatment partially attenuated the cell proliferation-promoting effect of miR-182-5p or miR-96-5p agomir treatment in HCC cells in vitro (Fig.…”
Section: Mir-182-5p or Mir-96-5p Increased Hcc Cell Mobility In Vitromentioning
confidence: 99%
“…The cell growth-inhibiting effect of RND3 overexpression has been demonstrated in esophageal squamous cell carcinoma cells, 23 while RND3 knockdown was found to enhance cell proliferation in glioblastoma cells and neural stem cells. 24,25 We therefore investigated whether miR-182-5p and miR-96-5p would inuence HCC cell growth in vitro by targeting RND3. Our cell viability and proliferation assay results both suggested that RND3 OE or TC-S 7001 treatment partially attenuated the cell proliferation-promoting effect of miR-182-5p or miR-96-5p agomir treatment in HCC cells in vitro (Fig.…”
Section: Mir-182-5p or Mir-96-5p Increased Hcc Cell Mobility In Vitromentioning
confidence: 99%
“…As for the four genes that are upregulated with youth and better NBL survival, only RND3 has a detailed research history with cancer. That cancer history is contradictory, as with other genes, with reports indicating a potential for high RND3 expression representing both pro- and anti-cancer results [2527]. A recent review regarding RND3 specifically evaluated the pro- and anti-cancer functions and concluded that indeed, the overall impact of RND3 is context dependent [28].…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype can be attributed to enhanced Notch signalling, which acts in coordination with proneural transcription factors to balance proliferation and differentiation of NSCs. Increased levels of the activated form of Notch (NICD: Notch intracellular domain) and of the Notch target Hes1 have been reported in the postnatal SVZ of Rnd3 knockouts and this increase is what drives the aberrant growth of NSCs, since Notch inhibition abolished the phenotype [30]. So, like in cortical basal progenitors, Rnd3 limits proliferation of SVZ progenitors, but the mechanisms involved are different.…”
Section: Svz Progenitorsmentioning
confidence: 99%
“…This effect, which is due to an upregulation of Notch signalling in these cells, blocks the cerebral aqueducts and leads to the development of hydrocephalus [18]. Moreover, Rnd3 knockout animals exhibit an enlarged and disorganized postnatal SVZ, which is due to increased NSC proliferation [28,30]. Since the SVZ contains neural stem and progenitor cells that produce new neurons over the course of adult life, aberrant SVZ neurogenesis might lead to long-term effect on adult neurogenesis and eventually contribute to mental disorders and/or neurodegenerative neurological disorders.…”
Section: In Pathological Conditionsmentioning
confidence: 99%